ChemInform Abstract: Asymmetric Synthesis of Dihydrofurans via Organocatalytic Domino Michael—Alkylation Reaction. Issue 34 (August 2015) - Feng, Juhua; Lin, Lili; Yu, Kunru; Liu, Xiaohua; Feng, Xiaoming
Abstract The asymmetric domino Michael‐alkylation reaction between cyclohexane‐1, 3‐dione derivatives and bromonitrostyrenes is efficiently catalyzed by a chiral N, N′‐dioxide organocatalyst.